Measurement validation for ICPS: Matrix pencil method for coriolis metering with liquid/gas flow - Ibryaeva, O; Semenov, A; Henry, M (IEEE, 2018)
A key requirement for Industrial Cyber-Physical System (ICPS) instrumentation is measurement validation i.e. assessing measurement quality, including detecting and correcting for fault conditions. Coriolis Mass flow meters are used widely throughout industry, but commonly only for singlephase fluids, i.e. either liquids or gases, since accuracy is degraded by gas/liquid flows. The provision of robust measurement in non-ideal conditions is an increasingly important requirement. Here we propose that a modified Matrix Pencil Method is able to track the modes of flowtube vibration excited by gas/liquid flow, and show the results of applying the technique to numerically simulated data.